The potter's field - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2011)
An unidentified corpse is found near Vigàta, a town known for its soil rich with potter's clay. Meanwhile, a woman reports the disappearance of her husband, a Colombian man with Sicilian origins who turns out to be related to a local mobster. Then Inspector Montalbano remembers the story from the Bible-- Judas's betrayal, the act of remorse, and the money for the potter's field, where those of unknown or foreign origin are to be buried-- and slowly, through myriad betrayals, finds his way to the solution to the crime.